PENGUKURAN AKTIVITAS METABOLISME BASAL PADA ITIK, ENTOG DAN MANDALUNG - Damayanti, Andi Pertiwi (AgriSains, 2005)
This experiment was done to test the basal metabolism activities of Cirebon ducks, Manila ducks and Mule ducks. To measure the basal activities such as O2 consumption, CO2 production, respiration quotient (RQ) and heat production there were 20 Cirebon ducks, Manila ducks and mule ducks. The measurement of three species was done three times, in which three ducks were measured at one week while another one was measured at four and eight weeks, respectively. Each measurement was replicated four times. The design used way completely randomized design with four groups as replication while species of duck was used as treatment. The data collected were analyzed with analysis of variant. Statistically, there were no differences in O2 consumption, CO2 production, heat production and quotient respiration in all species of ducks. However, biologically Cirebon duck in week four gained their energy from carbohydrate oxidation (93.6%) and from lipid (6.4%). Meanwhile, the Manila ducks and Mule ducks received all of their energy (100%) from carbohydrate oxidation (on week one, four and eight) and the Cirebon ducks which received all of their energy (100 %) from carbohydrate oxidation on week one and eight. Kata kunci : Basal Metabolism, Cirebon ducks, manila ducks, mule ducks